2017
DOI: 10.11138/mltj/2017.7.3.514
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patient functional performance in different knee arthroplasty designs during unconstrained squat

Abstract: SummaryBackground: In this paper, squat named by Authors unconstrained because performed without constrains related to feet position, speed, knee maximum angle to be reached, was tested as motor task revealing differences in functional performance after knee arthroplasty. It involves large joints ranges of motion, does not compromise joint safety and requires accurate control strategies to maintain balance. Methods: Motion capture techniques were used to study squat on a healthy control group (CTR) and on thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Differences in clinical outcomes between FB and MB prostheses has been reviewed with each study using different functional measurement indexes. Some studies 15,19 found better results in knee functional scores with the MB group, while Inoue et al 12 and Ozcan et al 11 found higher postoperative KSS in the FB group. Interestingly, Peersman et al 24 demonstrated that there was a tendency for the KSS to deteriorate more rapidly in MB than FB prostheses between 10 and 15 years.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Differences in clinical outcomes between FB and MB prostheses has been reviewed with each study using different functional measurement indexes. Some studies 15,19 found better results in knee functional scores with the MB group, while Inoue et al 12 and Ozcan et al 11 found higher postoperative KSS in the FB group. Interestingly, Peersman et al 24 demonstrated that there was a tendency for the KSS to deteriorate more rapidly in MB than FB prostheses between 10 and 15 years.…”
Section: Discussionmentioning
confidence: 96%
“…Two studies 1,20 found similar results between FB and MB groups in respect to pain (p > 0.05), however, Gleeson et al 5 reported that the total pain score, as assessed using the Bristol Knee Score, was significantly greater in the FB group at 2 years (p = 0.013). Postoperative ROM was assessed in five studies 9,12,15,19,20 , no significant difference was shown between the FB and MB groups (p = 0.19; WMD = − 1.53; 95% CI − 3.80 to 0.74).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study, which analyzed the squat movement using a 3D motion capture system, revealed significant differences in functional performance between patients with knee replacement and controls. For instance, a significant difference of 1.5s was found between TKA and controls for the duration of the descending part of the squat, or, a few mm of displacement in center of pressure mean distance has also been reported [17]. These differences can hardly be identified by visual observation alone and require more sophisticated equipment which is not readily available in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have been performed in the knee arthroplasty population and report a decrease in quadriceps activity and an increase in hamstring activation patterns during a squat, which lead to postural deviations in both the sagittal and the frontal plane. These deviations also resulted in an asymmetric transfer of the body weight to the lower limbs [17]. Nonetheless, it was demonstrated that TKA patients gradually evolve towards a more symmetrical loading of both knees as rehabilitation sessions progress.…”
Section: Introductionmentioning
confidence: 99%